The Effect of Thermal Treatment on the Concentration of Common Antibiotics in Cow Milk Samples in Sudan - Alawad, Tafaul Awad Mohamed; Behairy, Amira AbdelAzim; Elhag, Muhanad Mahmoud Abdullah; Saleem, Shakir (Journal of medical and pharmaceutical sciences, 2025)
Antibiotics in veterinary treatment have increased owing to intensive animal breeding for human consumption, resulting in antibacterial residues in food and potential health risks. This study examined how pasteurization and boiling affected the amounts of commonly used antibiotics—Tylosin (TYLO), Enrofloxacin (ENRO), Ampicillin (AMP), and Oxytetracycline (OTC)—in fresh cow milk. Cow milk samples without antibiotics were added with three antibiotic concentrations (3, 6, and 9 ppm). Each concentration was heat-treated twice and analyzed by Liquid Chromatography-Mass Spectrometry to determine antibiotic percentage reduction and kinetic degradation rate constants (k). The findings showed that all thermal treatments greatly reduced the initial antibiotic concentrations, with pasteurization being the most effective overall. Boiling raised k-values, suggesting faster deterioration. Boiling for 10 minutes works better than 5 minutes. For 5 minutes, there was a significant difference between pasteurization and boiling (P=0.002), but there was no significant difference after 10 minutes (P=0.09). TYLO decreased the most dramatically with pasteurization (49.3%-15%) as compared to boiling (30.4%-14.6%) and was much more influenced than OTC (46%-35.3%), ENRO (44.6%-32%), and AMP (30.6%-26.6%). The k-values for TYLO after pasteurization (0.0224 to 0.005) showed worse stability than other antibiotics. Boiling was very effective in lowering OTC concentrations (59%-15.3%), whereas ENRO and AMP showed the smallest decreases (11.6%-6.2% and 30.6%-26.6%, respectively). In summary, thermal treatments considerably reduced antibiotic concentrations in milk, with boiling displaying higher stability based on k-values, although pasteurization was more effective in terms of overall reduction based on breakdown rates. OTC had the most instability during boiling, while TYLO showed the least stability during pasteurization. AMP and ENRO were more stable over both treatments than OTC and TYLO, indicating that the effectiveness of thermal treatments is dependent on the individual antibiotic employed.